Head- and neck-related symptoms post-motor vehicle collision (MVC): Separate entities or two-sides of the same coin?. Issue 5 (May 2021) - Kuperman, Pora; Granovsky, Yelena; Fadel, Shiri; Bosak, Noam; Buxbaum, Chen; Hadad, Rafi; Sprecher, Elliot; Bahouth, Hany; Ben Lulu, Hen; Yarnitsky, David; Granot, Michal
Highlights: Not all patients with initial double diagnosis had 6-month head and neck disability. Chronic whiplash-related disability, explained solely by clinical pain variables. Clinical pain, gender and psychological factors influence post-concussion syndrome. Post-collision physical injury split into whiplash or mTBI may be a false dichotomy. Abstract: Background and Aim: Although post-motor vehicle collision (MVC) pain and symptoms are largely convergent among those with mild traumatic brain injury (mTBI) and whiplash associated disorder (WAD), and patients oftentimes report initial neck and head complaints, the clinical picture of mTBI and WAD has been primarily studied as separate conditions which may result in an incomplete clinical picture. As such, this study was conducted to explore the role of pain and post-traumatic psychological features in explaining both head and neck-related symptom variability in a cohort of post-collision patients. This is with the goal of disentangling if contributory factors are uniquely related to each diagnosis, or are shared between the two. Methods: Patients recruited in the very early acute phase (<72 h) returned for clinical and psychological assessment at 6 months post-accident. In order to determine which factors were unique and which ones were overlapping the same potential contributors: mean head pain, mean neck pain, female gender, number of post-collision painful body areas, PTSD, and depression were included in the regression models for both neck disability index (NDI) and Rivermead post-concussion symptoms questionnaire (RPQ). Results: Of 223 recruited participants, 70 returned for a follow-up visit (age range 18–64, mean(SD) 37.6 (11.9), 29F). This cohort primarily met the criteria for mTBI, but also fulfilled the criteria for whiplash, reinforcing the duality of injury presentation. Correlations existed between the NDI and RPQ scores (Spearman's ρ=0.66, p <0.001), however overlap was only partial. Regression analysis showed that after the removal of area-of-injury pain neck related disability ( r  = 0.80, p <0.001) was explained solely by number of painful body areas ( ß =0.52, p <0.001). In contrast, post-concussion syndrome symptoms ( r  = 0.86, p <0.001) are influenced by clinical pain, painful body areas ( ß =0.31, p  = 0.0026), female gender ( ß =0.19, p  = 0.0053), and psychological factors of depression ( ß =0.31, p  = 0.0028) and PTSD symptoms ( ß =0.36, p  = 0.0013). Conclusions: It seems that while mechanisms of neck- and head-related symptoms in post-collision patients do share a common explanatory feature, of residual body pain, they are not entirely overlapping. In that psychological factors influence post-concussion syndrome symptoms, but not post-whiplash neck disability.